1270 Secondary Survey Documentation in Trauma Patients - A Review Following Implementation of a Dedicated Trauma Ward. (12th October 2021) - Blacklock, C; Jones, K; Baker, G; Kealey, D
Abstract: Introduction: A secondary survey is a detailed head to toe assessment performed in trauma patients following initial primary survey and patient stabilisation. It forms part of the ATLS guidelines and is an important tool in the recognition of patient injury. We performed an audit within the Regional Trauma Unit to assess the standard of documentation of secondary surveys in trauma admissions. We then repeated this audit following staff teaching and the implementation of a dedicated Trauma Ward, with an aim of improving secondary survey documentation and the early recognition and management of associated injuries. Method: Admission notes for all trauma patients admitted in the three months prior to the opening of the dedicated Trauma Ward were reviewed for documentation of a secondary survey (n = 30), with the incidence of any missed injuries on follow up recorded. A further audit loop was then performed on all trauma admissions following the opening of the Trauma Ward and trauma staff teaching (n = 52). Results: Complete documentation of a full secondary survey improved from 10% to 98% for trauma patient admissions. This also improved early identification of initially missed injuries from the primary survey including extremity fractures, chest trauma, and multi-ligament knee injuries. Conclusions: Secondary surveys are an important tool in assessing trauma patients and can help identify significant injuries. The implementation of a dedicated Trauma Ward along with teaching to the trauma staff has led to an improvement in performance of secondary surveys with a direct improvement in identifying associated injuries in trauma patients.